# Difference between revisions of "Completing the Square"

Line 20: | Line 20: | ||

====Relationship between terms==== | ====Relationship between terms==== | ||

Note the relationship between the numbers in the factored form and the expanded form. The numbers available are 3, 6, and 9. The middle term of the quadratic is twice the constant of the binomial. The last term of the quadratic is the constant squared. In other words, <br> | Note the relationship between the numbers in the factored form and the expanded form. The numbers available are 3, 6, and 9. The middle term of the quadratic is twice the constant of the binomial. The last term of the quadratic is the constant squared. In other words, <br> | ||

− | <math>2\times3=6 and 3\times3=9</math> | + | <math>2\times3=6</math> and <math>3\times3=9</math><br> |

+ | In general given the perfect trinomial and the equivalent squared binomial <math>x^2+bx+c=(x+d)^2</math><br> | ||

+ | Then,<br> | ||

+ | <math>b=2d</math> | ||

+ | and | ||

+ | <math>c=d^2</math><br> | ||

+ | We can rearrange equalities to obtain the following: <math>c=(\tfrac{b}{2})^2</math> | ||

==Completing the Square== | ==Completing the Square== | ||

Let the quadratic equation be <math>ax^2+bx+c=0</math> | Let the quadratic equation be <math>ax^2+bx+c=0</math> | ||

Line 27: | Line 33: | ||

*Step 2: Factor out the coefficient of the squared term <br> | *Step 2: Factor out the coefficient of the squared term <br> | ||

<math>a(x^2+\frac{b}{a})=-c</math> | <math>a(x^2+\frac{b}{a})=-c</math> | ||

+ | *Step 3:Complete the quadratic in the paranthesis to make a perfect square trinomial. Remember that in general the constant of the perfect square trinomial is the square of half of the coefficient of x.<br> | ||

+ | <math>a(x^2+\frac{b}{a}+(\frac{b}{2a})^2)=a(x^2+\frac{b}{a}+\frac{b^2}{4a^2})</math> |

## Revision as of 14:36, 15 June 2009

## Contents

## The Basics

**Completing the Square** is a method commonly used to solve quadratic equations. Often times, a quadratic equation can be factored and solved easily. However, there are plenty of times when an equation is not factorable. By completing the square, a quadratic equation originally in standard form is rewritten into vertex form.

The equation

is converted into

through the process of **completing the square**.

## Perfect Square Trinomial

A **perfect square trinomial** is a big fancy word for a simple concept. It is a quadratic equation that factors perfectly into two identical binomials.

In general,

The quadratic on the right is a perfect square trinomial. It is the square of a binomial.

#### Example

Take the example of
. Using basic algebra, it can be factored into or

By completing the square, one of the components of the equation has to be a factored perfect square trinomial.

#### Relationship between terms

Note the relationship between the numbers in the factored form and the expanded form. The numbers available are 3, 6, and 9. The middle term of the quadratic is twice the constant of the binomial. The last term of the quadratic is the constant squared. In other words,

and

In general given the perfect trinomial and the equivalent squared binomial

Then,

and

We can rearrange equalities to obtain the following:

## Completing the Square

Let the quadratic equation be

- Step 1: Move the constant over to the other side of the equality

- Step 2: Factor out the coefficient of the squared term

- Step 3:Complete the quadratic in the paranthesis to make a perfect square trinomial. Remember that in general the constant of the perfect square trinomial is the square of half of the coefficient of x.